2004
DOI: 10.1093/jnci/djh169
|View full text |Cite
|
Sign up to set email alerts
|

Bone Sialoprotein, Matrix Metalloproteinase 2, and  v 3 Integrin in Osteotropic Cancer Cell Invasion

Abstract: Cancer cells appear to become more invasive when BSP forms a cell-surface trimolecular complex by linking MMP-2 to integrin alpha(v)beta3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 43 publications
2
100
0
7
Order By: Relevance
“…The formation of this complex leads to MMP activation and is thought to be important for invading cancer cells. 67 Furthermore, ON has been reported to induce activation of MMP2 and to regulate MMP9 expression in vivo. 20,68 Clearly, in our model extravasation of pancreatic cancer cells is a step which precedes their growth in the liver of nude rats.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of this complex leads to MMP activation and is thought to be important for invading cancer cells. 67 Furthermore, ON has been reported to induce activation of MMP2 and to regulate MMP9 expression in vivo. 20,68 Clearly, in our model extravasation of pancreatic cancer cells is a step which precedes their growth in the liver of nude rats.…”
Section: Discussionmentioning
confidence: 99%
“…BSP promoted invasion of several osteotropic cancer cell lines in vitro by apparently localizing MMP2 to the cell surface through αvβ3 (REF. 55). DMP1 enhanced the invasion potential of a colon cancer cell line by bridging MMP9 to integrins and, perhaps, CD44 (REF.…”
Section: Invasion and Extracellular Matrix Degradationmentioning
confidence: 99%
“…The cleaved lower molecular weight osteopontin fragments can penetrate into cells and have biological activities in promoting both cell adhesion and migration, but these are not observed for the intact osteopontin molecule (38). Thus, it was proposed that cleaved osteopontin may be a member of the SIBLING family of small integrin-binding ligand N-linked glycoproteins that can increase invasiveness of cancer cells by interacting with their specific matrix metalloproteinase and integrin partners, which was shown by a recent in vitro study (40). Our semiquantitative data clearly showed that COOHterminal osteopontin fragments were strongly correlated with ovarian cancer stages or invasiveness and support the previous findings.…”
Section: Discussionmentioning
confidence: 99%